When Leptin Is Not There: A Review of What Nonsyndromic Monogenic Obesity Cases Tell Us and the Benefits of Exogenous Leptin - Salum, Kaio Cezar Rodrigues; Rolando, Jônatas de Mendonça; Zembrzuski, Verônica Marques; Carneiro, João Regis Ivar; Mello, Cicero Brasileiro; Maya-Monteiro, Clarissa Menezes; Bozza, Patrícia Torres; Kohlrausch, Fabiana Barzotto; da Fonseca, Ana Carolina Proença (Frontiers in Endocrinology, 2021)
Obesity is a pandemic condition of complex etiology, resulting from the increasing exposition to obesogenic environmental factors, besides genetic susceptibility. In the past two decades, advances in genetic research identified variants of leptin-melanocortin pathway coding genes, which are related to the potentiation of satiety and hunger, immune system, and fertility. In this review, we listed the cases of congenital leptin deficiency and the beneficial effects of leptin replacement therapy available in the literature. This study discusses the cases of congenital leptin deficiency and the possible beneficial effects of leptin replacement therapy available in the literature. In summary, the cases showed clinical phenotype of disrupted body energy homeostasis, biochemical and hormonal disorders, and abnormal immunophenotype can be partially reversed by the exogenous leptin administration. With this review, we aim to contribute to the comprehension of leptin gene mutations as targets for obesity diagnostics and treatment strategies.